PENGARUH KOMPETENSI KERJA, KEPUASAN KERJA, DAN MOTIVASI KERJA APARATUR SIPIL NEGARA TERHADAP KINERJA PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN BOYOLALI (Studi Kasus pada SKPD di Kabupaten Boyolali) - Nur Azizah Wulandari; Haryanto Haryanto (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the influence of work competence, job satisfaction, and work motivation of Civil Servants (ASN) on the performance of regional financial management in Boyolali Regency. The research was conducted at Regional Government Work Units (SKPD) within the Boyolali Regency Government. The sampling technique used was stratified random sampling, in which the population of ASN was divided into several strata based on SKPD, and respondents were randomly selected from each stratum. The total number of respondents in this study was 50 civil servants who are directly involved in regional financial management activities. The data used were primary data obtained through the distribution of questionnaires. The data analysis method employed multiple linear regression analysis using SPSS version 29. Prior to hypothesis testing, the data were tested using validity and reliability tests, as well as classical assumption tests including normality, multicollinearity, and heteroscedasticity tests to ensure the feasibility of the regression model. The results of the study indicate that work competence and work motivation have a positive and significant effect on the performance of regional financial management, while job satisfaction does not have a significant effect. These findings suggest that improving competence and strengthening the work motivation of civil servants are important factors in enhancing the quality of regional financial management.